Determinasi Penggunaan E-Filing dengan Moderasi Kesiapan Teknologi Informasi - Aulia, Yoosita; Wahyuni, Putri (Akuntansi: Jurnal Akuntansi Integratif, 2020)
This study aims to determine the effect of speed of access and ease of system on the use of e-filing with the readiness of information technology as a variable moderation. The population used is the entire Individual Taxpayer in the KPP Mulyorejo Surabaya.Sampling technique uses purposive sampling, number of respondents are 100 individual taxpayers .Analysis technique in this study is Multiple Linear Regression. The results indicate the speed of access, ease of system has a positive effect on the use of e-Filing, readiness of information technology cannot moderate the effect of speed of access to the use of e-Filing, and readiness of information technology moderates the effect of ease of system on the use of e-Filing